CCAAT-enhancer binding protein-α (C/EBPα) and hepatocyte nuclear factor 4α (HNF4α) regulate expression of the human fructose-1,6-bisphosphatase 1 (FBP1) gene in human hepatocellular carcinoma HepG2 cells - Siriluck Wattanavanitchakorn (2019)
This is an open access article, free of all copyright, and may be freely reproduced, distributed, transmitted, modified, built upon, or otherwise used by anyone for any lawful purpose. The work is made available under the Creative Commons CC0 public domain dedication. Fructose-1,6-bisphosphatase (FBP1) plays an essential role in gluconeogenesis. Here we report that the human FBP1 gene is regulated by two liver-enriched transcription factors, CCAAT-enhancer binding protein-α (C/EBPα) and hepatocyte nuclear factor 4α (HNF4α) in human hepatoma HepG2 cells. C/EBPα regulates transcription of FBP1 gene via binding to the two overlapping C/EBPα sites located at nucleotide -228/-208 while HNF4α regulates FBP1 gene through binding to the classical H4-SBM site and direct repeat 3 (DR3) located at nucleotides -566/-554 and -212/-198, respectively. Mutations of these transcription factor binding sites result in marked decrease of C/EBPα- or HNF4α-mediated transcription activation of FBP1 promoter-luciferase reporter expression. Electrophoretic mobility shift assays of -228/-208 C/EBPα or -566/-554 and -212/-198 HNF4α sites with nuclear extract of HepG2 cells overexpressing C/EBPα or HNF4α confirms binding of these two transcription factors to these sites. Finally, we showed that siRNA-mediated suppression of C/EBPα or HNF4α expression in HepG2 cells lowers expression of FBP1 in parallel with down-regulation of expression of other gluconeogenic enzymes. Our results suggest that an overall gluconeogenic program is regulated by these two transcription factors, enabling transcription to occur in a liver-specific manner.